the first one is 8.5m2 + 2.2n ,, then the other person had the rest right . and number 3 could be 3x+1/3 ,, but it could also have different answers.
multiply x times y divide by 6 on both sides and you got your answer
Answer:
C
Step-by-step explanation:
f(x) - g(x)
= - x + 4 - (6x + 3)
= - x + 4 - 6x - 3 ← collect like terms
= - 7x + 1 → C
Answer:
=
Step-by-step explanation:
In this case in order to simplify we need to know what the "power rule of exponents" is. Simply speaking this rule states that when you raise a power to a power you multiply the exponents. So in our case we ill get the following
=
In order to get 42 we used the power rule which I mentioned earlier.